2016
DOI: 10.1097/md.0000000000005551
|View full text |Cite
|
Sign up to set email alerts
|

The FTO rs9939609 and LEPR rs1137101 mothers–newborns gene polymorphisms and maternal fat mass index effects on anthropometric characteristics in newborns

Abstract: The aim of this study was to assess the impact of mothers’ and newborns’ fat mass and obesity-associated gene (FTO) rs9939609 and leptin receptor (LEPR) rs1137101 gene polymorphisms on neonatal anthropometric parameters in order to identify a potential risk for developing obesity.We performed a cross-sectional study on 355 mother–newborn couples in an Obstetrics Gynecology Tertiary Hospital from Romania, evaluated with regard to anthropometric parameters, clinical and laboratory parameters besides 2 genetic po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
2
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 61 publications
3
19
2
2
Order By: Relevance
“…In our study, we attributed the non‐significant effect of the FTO gene on weight status to the lower number of participants in the 2nd follow‐up, mainly in the AA genotype group, which was the group with the smallest number of participants from the beginning. Moreover, the minor allele frequencies (MAFs) in our cohort study (baseline pre‐pregnancy: 0.33, first follow‐up: 0.29, and second follow‐up: 0.31) were lower than those found in other studies conducted on pregnant women (Marginean et al, ; Martins et al, ) and Brazilian individuals (Ramos et al, ) and in other cohort studies (Celis‐Morales et al, ; Frayling et al, ; Hallman et al, ; Qi et al, ). The low MAF may reduce the ability to see the real effect of the polymorphism due to the smaller number of women carrying at least 1 copy of the risk allele.…”
Section: Discussioncontrasting
confidence: 77%
“…In our study, we attributed the non‐significant effect of the FTO gene on weight status to the lower number of participants in the 2nd follow‐up, mainly in the AA genotype group, which was the group with the smallest number of participants from the beginning. Moreover, the minor allele frequencies (MAFs) in our cohort study (baseline pre‐pregnancy: 0.33, first follow‐up: 0.29, and second follow‐up: 0.31) were lower than those found in other studies conducted on pregnant women (Marginean et al, ; Martins et al, ) and Brazilian individuals (Ramos et al, ) and in other cohort studies (Celis‐Morales et al, ; Frayling et al, ; Hallman et al, ; Qi et al, ). The low MAF may reduce the ability to see the real effect of the polymorphism due to the smaller number of women carrying at least 1 copy of the risk allele.…”
Section: Discussioncontrasting
confidence: 77%
“…This pattern indicates that Q allele can contribute to the development of leptin resistance. The phenomenon we have established contradicts previously established postulates that R allele facilitates the development of leptin resistance (Sook-Ha, Yee How, 2014; Marginean et al, 2016). But these differences can be explained by ethnic characteristics, since most of these patterns were discovered on island populations.…”
Section: Resultscontrasting
confidence: 60%
“…Among those individuals, who have a higher body weight index, R-genotypes are more common. Other studies established that FTO rs9939609 and LEPR rs1137101 polymorphisms of parents affect the body weight and BMI of new born babies (Marginean et al, 2016). Thus, the Q223R can serve a molecular genetic marker of leptin resistance and can contribute to the development of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a recent study emphasized that a lower PI [i.e., PI, an index computed as birth weight (kg) divided by birth length (m) cubed] suggests that an individual is more vulnerable to the negative effects of the A risk allele of FTO polymorphism on body fat mass ( 34 ). In contrast, it was also shown that mothers carrying the variant A allele of rs9939609 FTO polymorphism had newborns with a lower BMI ( 9 ). Further functional studies are needed to determine the precise role of the FTO gene in determining obesity and its complications.…”
Section: Fat Mass and Obesity-associated (Fto) Gene And Obesitymentioning
confidence: 98%